2021
DOI: 10.3390/diagnostics11060933
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Mandibular Fractures in Panoramic Radiographs Using Deep Learning

Abstract: Mandibular fracture is one of the most frequent injuries in oral and maxillo-facial surgery. Radiologists diagnose mandibular fractures using panoramic radiography and cone-beam computed tomography (CBCT). Panoramic radiography is a conventional imaging modality, which is less complicated than CBCT. This paper proposes the diagnosis method of mandibular fractures in a panoramic radiograph based on a deep learning system without the intervention of radiologists. The deep learning system used has a one-stage det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…In the previously reported outcomes in the prototype application in radiology and pathology, precision and recall are approximately 87% to 93% and 65% to 88%, respectively. 4 , 8 Compared with previous studies, the precision score of the current model is slightly lower. This indicates that it is detecting regions other than the leak sites, creating FP cases.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the previously reported outcomes in the prototype application in radiology and pathology, precision and recall are approximately 87% to 93% and 65% to 88%, respectively. 4 , 8 Compared with previous studies, the precision score of the current model is slightly lower. This indicates that it is detecting regions other than the leak sites, creating FP cases.…”
Section: Discussioncontrasting
confidence: 71%
“…This framework has been previously applied to detect bone fractures and tumors in radiography. 3 , 4 However, it has not been applied to detect specific anatomical structures or organs during surgery. The algorithm is an open-source system that can show the existence and range of an object to be detected from an unknown image by examining the visual information.…”
mentioning
confidence: 99%
“…Recently, various algorithms such as the YOLO algorithm, deformable parts model, and R-CNN algorithm have been introduced and found to effectively detect cancer, nodules, fractures, or other lesions on medical images 31 34 . The YOLO algorithm was first proposed by Redmon et al 24 , and it has been applied in the dental field to detect various diseases on panoramic radiographs 17 , 29 , 35 , 36 . Yang et al 35 detected cysts and tumors of the jaw using YOLOv2 and obtained a precision of 0.707 and recall of 0.680.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al 17 developed a YOLOv3 model that showed high performance, with sensitivity values of 91.4%, 82.8%, 98.4%, and 71.7% for dentigerous cysts, periapical cysts, odontogenic keratocysts, and ameloblastomas, respectively. Son et al 36 developed a model to detect mandibular fractures using YOLOv4.…”
Section: Discussionmentioning
confidence: 99%
“…In oral and maxillofacial surgery, few studies have explored the capability of CNNs to detect mandibular fractures on PR automatically 10 , 21 . However, none of the studies has explored the detection and multi-classification (e.g., condyle, coronoid, ramus, paramedian, median, angle) of mandibular fractures on PR.…”
Section: Introductionmentioning
confidence: 99%